2005
DOI: 10.1074/jbc.m506131200
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Substrate Specificity of the C1s Protease of the Classical Complement Pathway

Abstract: The complement system is a central component of host defense but can also contribute to the inflammation seen in pathological conditions. The C1s protease of the first complement component, the C1 complex, initiates the pathway. In this study we have elucidated the full specificity of the enzyme for the first time using a randomized phage display library. It was found that, aside from the crucial P 1 position, the S 3 and S 2 subsites (in that order) played the greatest role in determining specificity. C1s pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 20 publications
(27 reference statements)
4
41
0
Order By: Relevance
“…Besides C4, C2, and the C1 inhibitor, only three other molecules, all expressed extracellularly, have been reported to be cleaved by C1s: insulin-like growth factor binding protein 5, MHC class I, and the Wnt coreceptor low-density lipoprotein receptor-related protein 6 (42)(43)(44). However, on the basis of a new C1s substrate formula established using a library of peptides centered around the known C1s cleavage sites in C4, C2, and the C1 inhibitor, many intracellular proteins have been predicted to contain C1s cleavage sites (33). The prediction was largely made on the basis of sequence preference and local secondary structures, on the basis of which NCL and NPM1 were both predicted to contain multiple C1s cleavage sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Besides C4, C2, and the C1 inhibitor, only three other molecules, all expressed extracellularly, have been reported to be cleaved by C1s: insulin-like growth factor binding protein 5, MHC class I, and the Wnt coreceptor low-density lipoprotein receptor-related protein 6 (42)(43)(44). However, on the basis of a new C1s substrate formula established using a library of peptides centered around the known C1s cleavage sites in C4, C2, and the C1 inhibitor, many intracellular proteins have been predicted to contain C1s cleavage sites (33). The prediction was largely made on the basis of sequence preference and local secondary structures, on the basis of which NCL and NPM1 were both predicted to contain multiple C1s cleavage sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The CCP1-CCP2-SP and SP fragments were inhibited with EGRck, an irreversible inhibitor targeted to the active site. EGRck would be expected to occupy the P3-P1 subsites of C1s, which were shown to be vital for interaction with cleavage sites in peptide and most likely protein substrates (30). The active site-inhibited CCP1-CCP2-SP fragment showed a 3-fold increased K D value in comparison with the active form ( Table I), suggesting that the active site played a small role in the binding of the enzyme to C4.…”
Section: The Active Site Of C1s Is Only Partially Responsible For Sp mentioning
confidence: 99%
“…Following electroporation, a total of 1.1 ϫ 10 8 CFU were obtained. While the number of individual clones in the library represents only a small fraction of the amino acid sequences obtainable from randomization of an octamer peptide (2.6 ϫ 10 10 ), it should nonetheless be sufficient to capture the key properties of amino acids preferred by the protease (11). Sequencing of 12 randomly selected clones from this library revealed that each contained an insert with a unique octamer amino acid sequence.…”
Section: Purification Of Omppmentioning
confidence: 99%
“…In particular, the specificities of over 30 proteases, spanning all recognized classes, have been studied by techniques relying on phage display (5,11,19,20). Substrate phage display is based on the selective cleavage of specific peptide sequences sandwiched between the gene pIII minor coat protein of fd bacteriophage and an affinity tag.…”
mentioning
confidence: 99%